Mechanism of engineered macrophage membrane bionic gene-carrying nanospheres for targeted drug delivery to promote wound repair in deep second-degree burns - Zhihan Zhu; Xinghua Zhu; Shichen Miao; Bolin Wang; Zihan Li; Dinghao Zhang; Shentian Zou; Yi Zhang; Qingrong Zhang; Kesu Hu (Scientific Reports)
Abstract Hepatocyte growth factor (HGF) is a substance that stimulates the proliferation of hepatocytes which promote healing. We developed a macrophage membrane-encapsulated nanosphere drug delivery system containing HGF for the study of burn wound healing. Twenty-seven Sprague–Dawley rats were randomly divided into three groups: a saline control (NS) group, an engineered macrophage membrane-encapsulated nanospheres (ETMM@NPS) group, and an engineered macrophage membrane-encapsulated nanospheres treatment with HGF-loaded gene (HGF@ETMM@NPS) group.The wound tissue sections were examined histologically using hematoxylin and eosin (H&E) and Masson trichrome staining. Immunohistochemistry and Western blotting were performed to determine the expression of relevant proteins. The wound-healing, blood flow and complete epithelialization rates were significantly better in the HGF@ETMM@NPS group compared to the NS and ETMM@NPS groups. Expression of B-cell lymphoma 2-associated X-protein was significantly lower, and B-cell lymphoma 2, cluster of differentiation 31, HGF, alpha smooth muscle actin, and PCNA expression was significantly higher in the HGF@ETMM@NPS group compared with the other two groups. PCNA and HGF expression was significantly up-regulated in the HGF@ETMM@NPS group. The HGF@ETMM@NPS complex drug delivery system used in this research promoted wound healing via effective delivery of HGF to burn wounds, thereby accelerating skin cell growth and migration.